Larval-damaged plants - source of volatile synomones that guide the parasitoid cotesia-marginiventris to the microhabitat of its hosts - Turlings, Ted; Tumlinson, James H; Eller, Fred J; Lewis, W Joe (My University, 1991)
Single and dual choice tests in a flight tunnel revealed that plants damaged by host larvae are the main source of the volatiles that attract females of the parasitoid Cotesia marginiventris (Cresson) to the microhabitat of its hosts. Frass and host larvae, the other two major components of a complete plant-host complex, were significantly less attractive than the damaged seedlings; frass alone was more attractive than larvae alone. However, a recombination of larvae with the damaged seedlings was significantly more attractive than the damaged leaves alone, or damaged leaves with frass. This was due to the additional feeding damage done by the larvae. The role of plants in the host-finding behaviour of parasitoids is discussed.
Keywords: HYMENOPTERA; BRACONIDAE; COTESIA-MARGINIVENTRIS; PARASITOID; HOST; SEARCHING; ALLELOCHEMICALS; PLANT SYNOMONES; LEAF DAMAGE; FRASS; FLIGHT; TUNNEL; CAMPOLETIS-SONORENSIS HYMENOPTERA; MICROPLITIS-CROCEIPES CRESSON; AIRBORNE SEMIOCHEMICALS; SPODOPTERA-FRUGIPERDA; FLIGHT BEHAVIOR; FALL; ARMYWORM; BRACONIDAE; HELIOTHIS; ICHNEUMONIDAE; LEPIDOPTERA